Comparing the Difficulty of Tasks Using Eye Tracking Combined with Subjective and Behavioural Criteria - Magdalena Andrzejewska; Anna Stolińska (Bern Open Publishing, 2016)
In this article, we attempted to examine the issue of the existence of differences in eye move-ment of school-age students as they solve tasks of different difficulty levels in the sciences and natural sciences (computer science, mathematics, physics, biology). Categories of the task's difficulty level were established on the basis of two types of criteria: subjective (an evaluation made by the subjects) and behavioural (connected to the correctness of their solution). The relationships of these criteria with the visual activity parameters, which were considered to be indicators of mental effort, were identified. An analysis of the data obtained enabled the observation of discrepancies in categorizing difficulties of the tasks on the basis of subjective and behavioural criteria. A significant and strong correlation was noticed between task difficulty level, determined by the percentage of correct answers, and the fixation parameters, although such a relationship with the blink parameters was not found. There was no correlation of the activity of the eye movement parameters, considered to be mental effort indicators, with a student's opinion about the task's difficulty level. On the basis of the investigations made, it can be stated that the fixation duration average can be taken as an index of the difficulty level of the task being solved.